Novel Porous Gold Microspheres Anisotropic Conductive Film (PGMS‐ACF) with High Compression Ratio for Flip Chip Packaging - Li Zhang; Zhaomeng Wang; Geng Wei; Puyue Xia; Sining Fan; Wenhao Zhang; Shaolong Tang (Advanced Electronic Materials)
Abstract The preparation of conductive filler is a key technology in anisotropic conductive films preparation. In recent decades, research on the preparation of novel conductive particles has reached a bottleneck. Porous gold materials exhibit high compressibility, low density, and excellent conductivity. It is believed that using porous gold microspheres (PGMS) to supersede polymer composite conductive microspheres has the potential to prepare anisotropic conductive film (ACF) with better performance. However, preparing ultrafine (1–10 µm) PGMS remains challenging. Herein, the study presents a novel method for preparing PGMS with controllable particle size and high sphericity. Results show that porous gold microspheres ACF (PGMS‐ACF), containing only 5 wt.% particles (size range 4.5–10.5 µm), achieves good conductivity when held at a pressure range of 0.05–0.6 MPa. Its compression ratio is between 33% and 71% at 0.3 MPa. The 4‐point probe measurement shows a contact resistance as low as 10 mΩ in 2 mm2. Moreover, PGMS‐ACF also exhibits a good linear relationship within 3.3 A. Compared to commercial polymer composite conductive microspheres ACF, PGMS‐ACF offers a significant advantage in achieving a large compression ratio, which in turn leads to improved conductivity and reduces the need for precise sorting. The research provides a new approach for the preparation of novel ACF.